Mauritius : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper assesses the external competitiveness of Mauritius over the period 1980-2007, with particular attention to the most recent years. The paper estimates the equilibrium real exchange rate using the macroeconomic balance approach, the single-equation equilibrium exchange rate approach, and the capital-enhanced equilibrium exchange rate approach. A wealth of structural competitiveness indicators are also analyzed. The findings indicate that the real exchange rate at the end of 2007 was broadly in line with its equilibrium value.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet